Burgomasters in Interwar Lithuania: Variety, Trends, Developments - Nekrašas, Leonas (Lietuvos istorijos studijos, 2025)
The article investigates peculiarities of the corpus of town and city burgomasters as an important Lithuanian urban settlement governance institution with regard to personalities, thus highlighting the related trends and their development. Sources allowed identifying 168 individuals who served as city or town burgomasters. Having collected data on them in more detail, the article explored this group regarding their age, nationality, education, professional activity and other features. On these grounds, the article focuses on changes in the trends along with peculiarities of performing the duties of a town burgomaster. This research is relevant for the cognition of the history of Lithuanian cities, towns and small towns, their governance and political life.